Right to a fair trial in international criminal proceedings - Mbuayang, Collins (2018)
"This book examines the right to a fair trial in international criminal proceedings from a human right perspective drawing mainly from General Comments, Individual Communications to the Human Right Committee and the jurisprudence of international criminal tribunals and courts. The author shows the extent to which international and hybrid criminal courts specifically ICTY and ICTR uphold human rights standards as lay down in the ICCPR. Even though these ad hoc tribunals have been criticized for lengthy trials, they have generously granted accused individuals enormous privileges such as the right to self-representation which is not possible in the ECtHR. To reconcile this situation, the author proposed that the ad hoc tribunals could adopt the approach of the ECtHR with regards to length of proceedings while the ECtHR can learn from the ad hoc tribunals with regards to self-representation."--Back cover
1 The Notion of Fairness and the Right to a Fair Trial -- 2 The Constitutive Elements to a Fair Trial -- 3 Balancing the Minimum Requirement to a Fair Trial -- 4 The Corollary of the Right to a Fair Trial -- 5 Application of the Right to a Fair Trial in International Criminal Law -- 6 Assessment of Cases in the Lens of the Right to a Fair Trial -- 7 Conclusions and Recommendations
Includes bibliographical references (pages 290-333) and index.
Keywords: Fair trial; International criminal courts; Proces equitable; Tribunaux penaux internationaux; Fair trial; International criminal courts; Faires Verfahren; Fair trial proceedings; International criminal courts and tribunals; International criminal procedure; International criminal justice